Analisis Validitas Liquid Mixer pada Trainer Smart Manufacturing Industry 4.0 (SMI) T201 - Faisal, Sadzali Perdana; Huda, Yasdinul (TSAQOFAH, 2025)
The Siemens S7-1200 PLC-based Liquid Mixer system, integrated into the Smart Manufacturing Industry 4.0 (SMI) T201 Trainer, was developed to automate the process of fluid filling and mixing through logical operations using actuators and sensors. This study aims to analyze the validity level of the system in the context of learning and training in smart manufacturing technology. The methodology employed is a quantitative approach with an evaluative design based on content validity analysis. Data were collected through 25 direct testing sessions with varying fluid volumes and performance evaluations using quantitative and evaluative instruments. The main results indicate that the system operates consistently and meets performance measurement standards. The validity score obtained using Aiken’s V formula is 0.94, indicating a high level of validity. The study concludes that the Liquid Mixer system demonstrates high accuracy and reliability in executing automation functions and makes a significant contribution to the development of PLC-based industrial automation systems in the field of smart manufacturing education and training.